#TITLE_ALTERNATIVE# - ARTANTA GINTING (NIM : 10106063); Dosen Pembimbing : Dr. Sri Redjeki, MARIA
In general, high buildings may sway or vibrate because of vibration, such as earthquake or storm. To reduce the vibration that may damage the buildings, there is a device called tuned mass damper (TMD). Buildings with TMD can be modeled as a mass spring with pendulum. In this system, the pendulum will act as damper that will reduce the vibration of the building. In this final project we formulate a system of second order differential equations for building with TMD. Building is assumed to be one mass that undergoes external vibration. Explicit solution of the equations directly shows the mechanism of TMD. The word tuned means, the natural frequency of damper should be equal to the natural frequency of the main system. In this way, we obtain the vibration amplitude of the main system as function of frequency. By applying TMD, the amplitude of the main system is reduced in the case of resonance or near resonance. For a better TMD, a dashpot can be added to the damper.